(untitled) (Journal of Parents and Teachers, 2014)
School mediation has become a very important tool in schools. This article explains the case of Carlos, a conflicted child, who attended the Meeduco program. In addition, there are guidelines that must be followed by a mediator and aspects that should not be done.